A Network Pharmacology and Molecular Docking Technology to Identify and Explore Mechanism of Bioactive Components of Fucus vesiculosus against Gut Disorders - Varisha Anjum; Uday Bagale; Ammar Kadi; Irina Potoroko (MDPI AG, 2024)
The gut is an intricate and diverse organ system for investigating visceral pattern generation. The gut made an early evolutionary breakthrough. There is evidence that the molecular mechanisms governing the development of gastrointestinal patterns are species-specific. Some have suggested using marine drugs to treat gastrointestinal disorders. The study, which used an integrated network pharmacology approach, aimed to find out how well fucoidan worked and what Fucus vesiculosus might be doing to help prevent digestive problems. Researchers gathered information on how potential bioactive components of brown seaweed and their associated targets interact with the disease gene targets of gastrointestinal disorders. We studied the signaling pathways linked to F. vesiculosus in the context of gut health treatments using a KEGG (Kyoto Encyclopedia of Genes and Genomes pathway) and GO (Gene ontology) enrichment analysis. We built and studied the protein-protein interaction (PPI) and compound-target networks using Cytoscape. PPI network analysis yielded a total of 44 important targets, including BCL2, ESR1, and STAT3. The KEGG enrichment analysis revealed a strong correlation between the signaling pathways used in the treatment and the prevention of gastrointestinal disorders. We docked significant genes with TNF, STAT3, BCL2, and ALB. Fucoxanthin and fucoidan possess beneficial properties for improving gut health by treating gastric-intestinal issues. This study showed that by controlling several targets and many pathways with multiple components, F. vesiculosus exhibited preventive effects against gastrointestinal disorders.